Influence of Demoxytocin on the Behavioural Actions of Melatonin - M. Selva Murugan, Manoj G. Tyagi* and (Journal of Experimental Sciences, 2011)
Oxytocin is stored and released by the posterior pituitary gland. In this study, the influence of oxytocin agonist, demoxytocin pretreatment on the behavioural actions of melatonin was ascertained. Swiss albino mice (n=6) were used for this study as control and test groups. Demoxytocin was injected in a concentration of (20 I.U/kg, i.p) and melatonin was injected (200mg/kg, i.p) 30 minutes before experimentation. The effect of pretreatment with demoxytocin was evaluated after melatonin injection on motor-coordination and locomotor activity. The results of our study suggest that demoxytocin was not able to affect significantly the actions on motor co-ordination but attenuated the locomotor activity after melatonin treatment.